2019
DOI: 10.1029/2019gl083294
|View full text |Cite
|
Sign up to set email alerts
|

Low Subsurface Water Storage Capacity Relative to Annual Rainfall Decouples Mediterranean Plant Productivity and Water Use From Rainfall Variability

Abstract: Plant water stress in response to rainfall variability is mediated by subsurface water storage, yet the controls on stored plant‐available water remain poorly understood. Here we develop a probabilistic water balance model for Mediterranean climates that relates the amount of water stored over the wet season to annual rainfall statistics and subsurface storage capacity in soil and weathered bedrock. This model predicts that low storage capacity—relative to winter rainfall—results in similar year‐to‐year summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
104
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 48 publications
9
104
0
1
Order By: Relevance
“…Several studies suggest that the responses of vegetation growing in seasonally dry climates to meteorological drought depend on the interactions between climate, subsurface hydrology, and landscape features. Hahm, Dralle, et al (), for example, demonstrate that in a subset of locations across California, limited subsurface water storage capacity, rather than variations in seasonal precipitation, appears to constrain plant productivity, such that variability in annual vegetation growth is independent of variations in annual precipitation. In Australian savannas, plant drought mortality varied by parent rock lithology (with mortality ranging from greatest to least across igneous metamorphic to sedimentary rock types to alluvium, Fensham & Holman, ), presumably reflecting differences in vadose zone porosity and permeability profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that the responses of vegetation growing in seasonally dry climates to meteorological drought depend on the interactions between climate, subsurface hydrology, and landscape features. Hahm, Dralle, et al (), for example, demonstrate that in a subset of locations across California, limited subsurface water storage capacity, rather than variations in seasonal precipitation, appears to constrain plant productivity, such that variability in annual vegetation growth is independent of variations in annual precipitation. In Australian savannas, plant drought mortality varied by parent rock lithology (with mortality ranging from greatest to least across igneous metamorphic to sedimentary rock types to alluvium, Fensham & Holman, ), presumably reflecting differences in vadose zone porosity and permeability profiles.…”
Section: Introductionmentioning
confidence: 99%
“…As the climate warms, increase in plant water use in Mediterranean climates due to higher‐energy availability in spring can be offset by decreases due to soil limitation in summer (Pangle et al, ; Tague & Peng, ), a phenomena consistent with global trends (Angert et al, ; Buermann et al, ; Wolf et al, ). This temporal alignment of seasonal water and energy availability (or its change) also influences partitioning of subsurface water resources between groundwater recharge, transpiration, and streamflow (Dralle et al, ; Hahm et al, ). Additionally, in Mediterranean climates that are snow‐dominated, warming reduces the fraction of precipitation that falls as snow and promotes earlier snowmelt (which is slower and less likely to saturate soils; Musselman et al, ): all changes that tend to increase evapotranspiration at the expense of streamflow (Barnhart et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hahm et al (2019b) recently revealed through intensive hillslopescale monitoring in the Northern California Coast Ranges how the magnitude of plantavailable water storage is capped by subsurface water storage capacity, which is in turn related to the depth and extent of weathering in the CZ. Hahm et al (2019a) also demonstrated, via remote-sensing of plant greenness and water-balance tracking, that subsurface water storage capacity can decouple summer water availability, and thus plant productivity, from year-toyear rainfall variability. However, methods and datasets that explicitly map CZ structure are generally lacking at larger spatial scales, or have limited applicability.…”
Section: Introductionmentioning
confidence: 92%
“…In the Results, we demonstrate that knowledge of CV [S 0 ] = CV [ET dry ] can be used to directly estimate S max . This method for estimating storage is more widely applicable than the flux-tracking methodology presented in Hahm et al (2019a), because it does not rely on closure of the water budget which, crucially, requires unimpaired stream gauging. Moreover, the storage capacities that could be inferred from flux tracking are total catchment dynamic water storages, rather than root-zone plantavailable water storage capacities, which is estimated here.…”
Section: Model Inversion For Estimating S Maxmentioning
confidence: 99%
See 1 more Smart Citation